(untitled) (Research, Society and Development, 2021)
The water balance is used to assess climatic parameters and to adapt species from favorable climates to the suitability of a given area for the monopoly of local culture. The objective is to determine the climatic aptitudes of the cultivars: sugarcane, banana, beans, corn, castor bean, cassava, sisal, pineapple, herbaceous cotton, sorghum and mango, classifying the aptitudes for planting in the studied area and its classification in order to minimize soil loss through erosion. Rainfall and thermal data were provided by the sergipe state rural assistance and extension company for the period 1963-2019. Pineapple crops; herbaceous cotton; beans and sisal have full fitness; castor bean; manioc; mango; sugar cane; cashew; maize and sorghum its aptitudes were moderate and the banana crop with restricted aptitude in some areas; forage palm restricted to some areas due to excess water. Mango cultivars; cashew; forage palm and banana should be planted at different spacing, following the order of the cultivars mentioned, so that they can have better soil fixation, avoiding dragging by erosion.